Accelerated rejection of the second transplants of immunogenic tumor in mice under inhibition of indoleamine 2,3-dioxygenase activity by ethyl pyruvate - Vasilyeva, E.D.; Kaledin, V.; Nikolin, V.P.; Popova, N.A.; Kirilyuk, I.A.; Grigor`ev, I.A. (Experimental Oncology, 2012)
Aim: A recently discovered enzyme, indoleamine 2,3-dioxygenase (IDO), is expressed in placenta, dendritic cells and also in many kinds of tumors and in tumor-infiltrating macrophages. By catabolizing tryptophan, IDO causes local depletion of this essential amino acid and excess of kinurenin, and suppresses in situ proliferation and functioning of T lymphocytes. Thus, immune resistance of tumors can be overcome by inhibiting IDO activity. Materials and Methods: C3HA mice immunized with non-syngeneic H-29 tumor were used to study the effect of the IDO inhibitor ethyl pyruvate, under systemic or local (at site of tumor cells localization) administration, on the occurrence and rate of rejection of the second transplants of this tumor. Results: Both systemic and local administration of ethyl pyruvate increases the incidence of and substantially accelerates tumor regression as compared with control. Conclusion: IDO inhibitors impairing immune resistance of tumors may appear useful in leveraging the efficacy of antitumor therapy.